Medicina Ancestral en el tratamiento de las infecciones respiratorias en el Subcentro 24 de mayo - Cantón Montalvo, Provincia de Los Ríos, Octubre 2019 Marzo 2020. - Espinoza Espinoza, Dolores Yelen (2020)
Ancient medicine is a whole set of knowledge, based on theories, indigenous beliefs from different cultures. Respiratory infections are infectious diseases plus the most be human representing less than 15 days of evolution. The main objective of demonstrating the impact of ancestral medicine on communities with respect to the use, benefits and treatment of respiratory infections in adults in the Subcenter "May 24" in the city of Montalvo during the period of October 2019 – March 2020. The methodology to be decriminalised, field, documentary, transversal and correlational. At the end of this research, the following results were reached where ancestral medicine is not as used because of the unconsciousness of the patients that there is a high rate of morbidity as mortality from respiratory infections in the patients entering the health center. Due to excessive administration of medicines and these cause adverse effects over time, patients look for another alternative such as ancestral medicine, but many do not have the value of use s avoid slight harm. In conclusion, treatment for respiratory infections has to be in the background, due to a lack of knowledge of me than the higher percentage of side effects of 82% by Western medicine. This leads us to the development of a preventive measure as a guide to the preparations of ancestral medicine on the use and its benefits in the treatment of respiratory infections in patients in the Subcenter "24 Of May", where it is expected to avoid increase the mortality and morbidity rate and raise awareness and educating the community.